Secondary metabolites as DNA topoisomerase inhibitors: A new era towards designing of anticancer drugs - Baikar, Supriya; Malpathak, Nutan (Pharmacognosy Reviews, 2010)
A large number of secondary metabolites like alkaloids, terpenoids, polyphenols and quinones are produced by the plants. These metabolites can be utilized as natural medicines for the reason that they inhibit the activity of DNA topoisomerase which are the clinical targets for anticancer drugs. DNA topoisomerases are the cellular enzymes that change the topological state of DNA through the breaking and rejoining of DNA strands. Synthetic drugs as inhibitors of topoisomerases have been developed and used in the clinical trials but severe side effects are a serious problem for them therefore, there is a need for the development of novel plant-derived natural drugs and their analogs which may serve as appropriate inhibitors with respect to drug designing. The theme for this review is how secondary metabolites or natural products inactivate the action of DNA topoisomerases and open new avenues towards isolation and characterization of compounds for the development of novel drugs with anticancer potential.
Keywords: Anticancer; DNA topoisomerases; secondary metabolities; flavonoids